A Host–Guest Electron Transfer Mechanism for Magnetic and Electronic Modifications in a Redox‐Active Metal–Organic Framework. Issue 18 (2nd March 2022) - Zhang, Jun; Kosaka, Wataru; Kitagawa, Yasutaka; Miyasaka, Hitoshi
Abstract: Host–guest electron transfer (HGET) in molecular framework systems is a critical trigger for drastic functional changes in both host framework and guest. A reversible magnetic phase transition was achieved via HGET in a layered framework, [Ru2 (2, 6‐F2 PhCO2 )4 2 (BTDA‐TCNQ)] (1 ), where 2, 6‐F2 PhCO2 − and BTDA‐TCNQ represent 2, 6‐difluorobenzoate and bis[1, 2, 5]dithiazolotetracyanoquinodimethane, respectively. The guest‐free 1 with an antiferromagnetic ground state transformed into a paramagnet, [Ru2 (2, 6‐F2 PhCO2 )4 2 (BTDA‐TCNQ)]I3 (1‐I3 ), by adsorbing iodine (I2 ). The local charge distribution of [Ru2 II, III + ‐(BTDA‐TCNQ) .− ‐Ru2 II, II ] in 1 was reversibly modified to [Ru2 II, III + ‐(BTDA‐TCNQ) 0 ‐Ru2 II, II ](I3 − ) in 1‐I3 through HGET. Theoretical calculations of 1‐I3 indicated a partial charge delocalization as [Ru2 (1− δ )+ ‐(BTDA‐TCNQ) 0 ‐Ru2 δ + ](I3 − ) with δ ≈0.2, aided by weak ferromagnetic coupling. 1‐I3 exhibited a hundred‐fold enhancement in electrical conductivity compared to that of 1 . Abstract : The first reversible magnetic phase switch between antiferromagnet and paramagnet has been achieved through host–guest electron transfer via I2 ‐vapor sorption. The partial charge delocalization was formed in the I2 ‐loaded framework, resulting in a hundred‐fold increase in electrical conductivity via hopping electronic transport.